The Equivalence in Religion-Related Outdoor Text on Signboards in Denpasar City - Baharuddin (e-Journal of Linguistics, 2023)
In today's society, travel is inevitable. With international visitor arrivalsreaching 1,4 billion in 2018, almost one-fifth of the world's populationtravels abroad. Travelers must have access to accurate informationabout their destination. Signage posted in several locations to replacethe information desk workers must be tailored to minimize misleadingmisinformation. This page examines religious signs or signage inDenpasar, the capital of the globally renowned province of Bali,Indonesia. In this article, questions are raised regarding the equality ofreligious text meanings in the Indonesian-English translations ofDenpasar's signage. Photographs of nameboards and information weretaken in four sub-districts to collect data, which was then examinedfrom the standpoint of linguistic landscapes and translation science. Theinformation is shown as text or outdoor signs. The study of the dataindicates that the equivalent translation of the bilingual versions of thetext is acceptable, with the exception of the linguistic structure. On theother hand, textual material can be regarded culturally, functionally,and descriptively acceptable, but the language of the content on presentwebsites requires refinement.